Development of Physics Learning Media Integrated with Rebuttal Text (PhyLeM-ReT) on Work and Energy Material - Kurniasih, Lutfi; Samsudin, Achmad; Aminudin, Ahmad (Berkala Ilmiah Pendidikan Fisika, 2025)
This study aimed to develop Physics Learning Media assisted by Rebuttal Texts (PhyLeM-ReT), integrated with the Predict, Observe, Explain, Apply, and Write (POEAW) model for work and energy material. The development research design employed in this study was ADDIE (Analysis, Design, Development, Implementation, and Evaluation). The participants were 30 tenth-grade students from a private high school in Bandung. A student response questionnaire to the media was implemented, which comprised 19 statements (10 positive and nine negative) and was evaluated using a Likert scale. This study implemented Rasch analysis. The result showed that 25 students agreed with the positive statements and disagreed with the negative statements related to interest in learning physics, the use of media, enthusiasm for learning, and usefulness in understanding concepts. Thus, PhyLeM-ReT integrated with the POEAW model facilitates students' comprehension of energy and work material. The developed media can also serve as an alternative for teachers in teaching, specifically enhancing and transforming students' conceptions. This research is crucial in an era where misconceptions regarding physics persist, as it aims to offer effective alternative learning media that can address these obstacles. Additionally, this research presents opportunities for further development in integrating comparable methods into other subject areas of physics that necessitate a profound conceptual approach.